Human antigen R promotes angiogenesis of endothelial cells cultured with adipose stem cells derived exosomes via overexpression of vascular endothelial growth factor in vitro. (1st January 2021) - Li, Guo; Chen, Youbai; Han, Yudi; Ma, Tian; Han, Yan
ABSTRACT: Recent studies showed that exosomes obtained from adipose-derived stem cells (ADSCs) could improve the angiogenesis of fat grafts via overexpression of vascular endothelial growth factor (VEGF). Human antigen R (HuR) promotes the expression of VEGF in many cancers, but the effect of HuR in normal endothelial cells in the presence of ADSC-derived exosomes remains unclear. We aimed to investigate the effect of HuR on the expression of VEGF and angiogenesis of human umbilical vein endothelial cells (HUVECs) cultured with ADSCs-derived exosomes. The HuR-overexpressed HUVECs (HuR-HUVECs) were cocultured with ADSCs-derived exosomes. qRT-PCR and Western blotting were performed to examine the stability and expression of VEGF-A mRNA and protein. The proliferation, migration, and proangiogenic capacity of HuR-HUVECs were evaluated using cell counting kit-8 (CCK-8), scratch wound healing, and Matrigel tube formation assay. qRT-PCR showed that HuR-HUVECs had higher expression and slower attenuation of VEGF-A mRNA. Western blotting confirmed higher expression of VEGF-A in HuR-HUVECs. CCK-8, scratch wound healing, and Matrigel tube formation assay demonstrated an increased proangiogenic effect in HuR-HUVECs. HuR promotes angiogenesis of HUVECs cocultured with ADSCs-derived exosomes via stabilization and overexpression of VEGF in vitro. The HuR/VEGF pathway is an important regulatory mechanism of angiogenesis in endothelial cells.